2013
DOI: 10.1194/jlr.m037416
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses by mouse fetus to a maternal HLE diet by downregulating SREBP1: a microarray- and bio-analytic-based study

Abstract: health problems as the ones observed in epidemiological studies ( 4,5 ). So, maternal high-fat diet is an important predisposing factor to the onset and development of obesity, insulin resistance, and cardiovascular diseases in offspring ( 6 ). Indeed, a high-fat diet during gestation has been shown to lead to a lack of increase in insulin release and ATP content in response to glucose stimulation in islets from 3-month-old male and female offspring ( 5 ).However, the mechanisms linking high-fat nutrition in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Srebp1 is a key transcription factor and Fasn is the key enzyme of lipogenesis [30,43]. The expression of the Elovl3 is under the control of PPARα [44].…”
Section: Resultsmentioning
confidence: 99%
“…Srebp1 is a key transcription factor and Fasn is the key enzyme of lipogenesis [30,43]. The expression of the Elovl3 is under the control of PPARα [44].…”
Section: Resultsmentioning
confidence: 99%
“…The association between maternal prepregnancy overweight and obesity and offspring BMI, which persists after adjustment for genetic and lifestyle factors, supports previous research describing intergenerational inheritance of metabolic outcomes beyond the inheritance of genetic sequence variants and learned behavior. Although the mechanism underlying fetal programming of obesity is not fully understood, both animal and human models examining the fetal overnutrition hypothesis have supported a possible epigenetic link between maternal and offspring adiposity . Numerous genomic regulatory mechanisms have been implicated in the intergenerational epigenetic inheritance of metabolic disease, including nuclear and ribosomal DNA methylation, histone modifications, and noncoding microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genomic regulatory mechanisms have been implicated in the intergenerational epigenetic inheritance of metabolic disease, including nuclear and ribosomal DNA methylation, histone modifications, and noncoding microRNAs. In murine models, maternal obesity has been associated with differential methylation of genes involved in fatty acid, cholesterol, and glycogen metabolism . In mammalian fetal models, microRNAs previously linked to CVD and insulin signaling have been differentially expressed among animals exposed to maternal obesity compared with mothers with normal weight .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed downregulation of SREBP signaling is in agreement with two previous studies that examined the effect of a maternal HF diet on offspring livers. These studies reported that SREBP gene and protein expression were diminished and that this regulated the observed decrease in mRNA expression of genes involved in fatty acid, cholesterol, and steroid biosynthesis, and other SREBP-related functions (45, 46). In contrast, two other studies found an increase in mRNA expression of Srebp1c and some of its downstream genes involved in de novo lipogenesis in response to a prenatal HF diet (13, 14).…”
Section: Discussionmentioning
confidence: 96%